2007
DOI: 10.1002/jcp.21229
|View full text |Cite
|
Sign up to set email alerts
|

Flow‐dependent regulation of angiopoietin‐2

Abstract: Endothelial cells are constantly exposed to high or low shear stress in arteries and veins by the flowing blood. Angiopoietin-2 (Ang-2) is acting as a critical regulator of vessel maturation and endothelial cell quiescence. In this study, flow-dependent regulation of Ang-2 was analyzed in vitro and in vivo. Ang-2 mRNA, protein expression and release was upregulated by 24 h of low (1 dyne/cm(2)), but downregulated by high flow (30 dyne/cm(2)) in human endothelial cells. Increased endothelial NO synthase express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 59 publications
7
62
0
Order By: Relevance
“…Interestingly, ANG-2 is also regulated by mechanical shear-stress on ECs. FoxO1 and KLF2 have been shown to play a role in mediating ANG-2 regulation by shear-stress in different ways 40,41 . Considering the recent finding that YAP plays a key role in cellular mechanotransduction, it is not surprising that ANG-2 is regulated by YAP in ECs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ANG-2 is also regulated by mechanical shear-stress on ECs. FoxO1 and KLF2 have been shown to play a role in mediating ANG-2 regulation by shear-stress in different ways 40,41 . Considering the recent finding that YAP plays a key role in cellular mechanotransduction, it is not surprising that ANG-2 is regulated by YAP in ECs.…”
Section: Discussionmentioning
confidence: 99%
“…FACS analysis showed that Ang-1 binding was unaffected by pan-integrin inhibitor EDTA, suggesting that Ang-1 fails to interact with monocyte integrins. More recently, low-shear flow conditions were identified to increase the expression of Ang-2 in human endothelial cells, 22 and Ang-2 potentiates TNF-␣-induced monocyte adhesion. 23 In FACS-based binding, we show that Ang-1, but not Ang-2, binds to monocytes, whereas both Ang-1 and Ang-2 bind to HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in cultured ECs revealed that laminar flow prompts PI3K-AKTdependent inactivation of FOXO1. 68,69,70 AMPK has also been implicated in flow-mediated inhibition of FOXO1. 68 Whether this inhibitory effect requires the direct phosphorylation of FOXO1 by AMPK must be determined.…”
Section: Foxos and Sirtuins In Vascular Maintenance And Homeostasismentioning
confidence: 99%